2011
DOI: 10.1007/s12094-011-0738-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytopathology in the diagnosis of Wilms tumor

Abstract: BACKGROUND/PURPOSE The International Society of Paediatric Oncology (SIOP) protocol for Wilms tumor (WT) includes preoperative chemotherapy as the initial approach. However, an inadequate treatment may be performed in case of histological misdiagnosis. We evaluated the impact of fine-needle aspiration cytopathology (FNAC) in the diagnosis of unilateral WT in our group of patients. MATERIALS AND METHODS A retrospective descriptive study of patients with diagnosis of unilateral WT who underwent FNAC prior to neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…When required, both FNA and CNB techniques provide adequate samples. The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB) . However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When required, both FNA and CNB techniques provide adequate samples. The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB) . However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
“…The cellularity was judged satisfactory in 82% to 85% of our cases, in agreement with the literature (i.e., 76% to 93% for FNA and 80% to 95% for CNB). [13][14][15]17,[45][46][47][48][49][50][51] However, our data confirm a significantly higher diagnostic accuracy of CNB, as previously reported. 13,[15][16][17][18]52,53 Nevertheless, in our experience, FNA remains useful in several settings: it allows extemporaneous examinations during the procedure, helping physicians performing biopsies to adjust the amount of tissue to be obtained.…”
Section: However the Relevant Tumor Volume Threshold Below Which A Bsupporting
confidence: 92%
“…Thus, cell blocks often showed additional epithelial or mesenchymal This is concordant with a previous study by Alam et al and higher than the reported sensitivity of 95% by Fernández-Pineda et al 8,14 In comparison, a recent trial in UK by Jackson et al showed 86% sensitivity for CNB requiring repeat biopsies. 15 Furthermore, there is a theoretical possibility and one case report in the literature regarding needle tract seeding after CNB.…”
Section: Cell Blocks In Wtsupporting
confidence: 88%
“…In the 2001 SIOP WT protocol, FNABC for providing a cellular diagnosis prior to chemotherapy was allowed with no risk of upstaging. 8 In majority of these cases, FNABC is amenable without any anaesthesia and has an advantage of low cost, early diagnoses, minimal invasiveness and lesser contraindications. Previous studies have documented the cytomorphology of WT on FNABC samples, [9][10][11][12] including the distinction of WT from other uncommon paediatric renal neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Fernandez-Pineda et al found FNAB to be a very valuable technique to confirm the diagnosis of Wilms tumor. The sensitivity and specificity of FNAB was found to be 95% and 83.3% respectively [ 10 ].…”
Section: Main Textmentioning
confidence: 99%